(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article discusses the impact of leadership, empathy, altruism, social responsibility, and optimistic outlooks on enhancing team effectiveness. It describes how leaders with the traits of the «Bright Triad» maintain a high moral climate within the team, help achieve common goals, and sustain motivation. Altruistic and empathetic leaders build trust within the team, which contributes to success. The article also emphasizes the high effectiveness of such leaders in improving teamwork and overall productivity.